Heat Shock Proteins: Mediators of Atherosclerotic Development - F. Deniset, Justin; N. Pierce, Grant (Current Drug Targets, 2015)
Heat shock proteins play important housekeeping roles in a variety of cells within the body during normal control conditions. The many different functions for heat shock proteins in the cell depend upon the specific heat shock protein involved. Each protein is nominally differentiated based upon its molecular size. However, in addition to their role in normal cell function, heat shock proteins may play an even more important role as pro-survival proteins conserved through evolution to protect the cell from a variety of stresses. The ability of a cell to withstand these environmental stresses is critical to its capacity to adapt and remain viable. Loss of this ability may lead to pathological states. Abnormal localization, structure or function of the heat shock proteins has been associated with many pathologies, including those involving heart disease. Heat shock proteins like HSP60 and HSP70 in particular have been identified as playing important roles in inflammation and immune reactions. Inflammation has been identified recently as an important pathological risk factor for heart disease. It is perhaps not surprising therefore, that heat shock protein family has been increasingly identified as an important intracellular pathway associated with inflammatory-mediated heart conditions including atherosclerosis. This paper reviews the evidence in support of a role for heat shock proteins in cardiovascular disease and the potential to target these proteins to alter the progression of atherosclerotic disease.
Keywords: inflammation